Characterization of Achlya americana and A. bisexualis (Saprolegniales, Oomycota) Isolated from Freshwater Environments in Korea - Choi, Young-Joon (Mycobiology, 2019)
Many members of the Saprolegniales (Oomycete) cause mycoses and disorders of fishes, of which Achlya and Saprolegnia are most ubiquitous genera worldwide. During a survey of the diversity of freshwater oomycetes in Korea, we collected seven isolates of Achlya, for which morphological and molecular phylogenetic analyses enabled them to identify as Achlya americana and Achlya bisexualis. In Korea, only a species of Achlya, A. prolifera, has been previously found to cause seedling rot on rice (Oryza sativa), but none of the two species have been reported yet. Importantly, A. bisexualis was isolated from a live fish, namely rice fish (Oryzias sinensis), as well as freshwater, and this is the first report of Achlya-causing mycoses on freshwater fishes in Korea. The presence of A. americana and A. bisexualis on live fish in Korea should be closely monitored, as considering the well-known broad infectivity of these species it has the potential to cause an important emerging disease on aquaculture industry.